Pengaruh Model Problem Based Learning (PBL) berbantuan Video Pembelajaran terhadap Kemampuan Pemecahan Masalah Matematis - Sariayu Sibarani; Rusmini Rusmini; Ratna Natalia Mendrofa; Hasratuddin Hasratuddin (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
This research aims to determine the influence and magnitude of the Problem Based Learning (PBL) Model using learning videos on mathematical problem solving abilities in two-variable linear system equations. This research is a quasi-experimental research with a pretest-posttest control group design, where the class is the experimental class, and the class is the control class. The data collection technique is in the form of pretest and posttest results given to two research classes. Next, the t test is carried out to test the hypothesis after first passing the prerequisite tests, namely the normality test and homogeneity test. The results obtained show that learning with the PBL model assisted by learning videos has an effect on mathematical problem solving abilities. Students taught using the PBL model assisted by learning videos have higher problem solving abilities compared to those taught using the direct learning model. The magnitude of the treatment effect shows that there is a high influence and consistency of the PBL model assisted by learning videos on mathematical problem solving abilities.